Frontotemporal Dementia-Associated N279K Tau Mutation Localizes at the Nuclear Compartment - Ritter, Maxi L.; Avila, Jesús; García-Escudero, Vega; Hernández, Félix; Pérez, Mar (Frontiers in Cellular Neuroscience, 2018)
Tau is a microtubule-associated protein that plays an important role in Alzheimer’s disease and related tauopathies. Approximately one-half of all cases of Frontotemporal dementia with parkinsonism-17 (FTDP-17) are caused by mutations in the MAPT gene. The N279K mutation is one of the three mutations more prevalent in FTDP-17 cases. Several studies have demonstrated that N279K Tau mutation alters alternative splicing inducing the presence of exon 10. Tau is mainly found in the cytosol of neuronal cells although it has also been localized within the nucleus. Here we demonstrate by biochemical and immunohistochemistry studies in COS-7 cells, that the proportion of mutant N279K Tau increases compared with wild-type at the cell nucleus although cell viability is not affected. These data will provide us with a better outline of the nuclear role of tau protein offering new clues related with this tauopathie.